MODERN SOCIAL AND PSYCHOLOGICAL PROBLEMS OF MEDIATOR’S ACTIVITY IN LEGAL CIVIL RELATIONS - Manukyan, H.V. (Modern Psychology, 2019)
Raising legal awareness in modern society will undoubtedly contribute to improving the quality of human life. However, at the same time, in interpersonal and intergroup relationships there is an increase in the number of household, family, administrative, constitutional and legal other types of dispute. Therefore, there is a need to find new mechanisms and opportunities for civil litigation, including mediation, which is widely used in the developed countries of Europe and America. In Armenia, mediation is at an early stage of its development, and this circumstance makes it necessary to undertake scientific research and a comprehensive analysis of the process of mediation. The purpose of this study is to analyze the socio-psychological characteristics of the activities of the mediator and the search for adequate means of professional psychological mediation schemes.
Keywords: Mediator, mediation, civil and law relations, socio-psychological problems.